Strategi Regulasi Emosi Pada Individu Dewasa Awal Yang Mengalami Sleep Deprivation - Mahendra Putri, Shafa Shafira; Pradna Paramita , Pramesti (Jurnal Syntax Fusion, 2023)
The purpose of this research is to find out and understand how young adults who experience sleep deprivation regulate emotions. This research uses a qualitative method with an intrinsic case study approach to look at a case in more depth based on the researcher's internal interests. The data in this research were analyzed using thematic analysis with data driven. Subjects in this study are four people who were selected based on the criteria set by using purposive sampling. The data collection process in this research used a semi-structured interview method. The interviews conducted were flexible and open. The credibility technique in this research uses member checks. The results of this research found that the emotional condition of subjects who experienced sleep deprivation became worse due to internal and external factors. Emotional regulation strategies carried out by the subject include being aware of emotional conditions, regulating body responses (hiding the emotions felt), leaving situations that evoke emotions (after emotions were felt), avoiding conditions that evoke emotions (before emotions were felt), overflowing emotions, diverting attention from situations that evoke emotions, open to the external environment, accept the situation, analyze environmental conditions, and physical rejection. As for external factors that further enhance the subject's ability to regulate emotions such as a supportive environment, conducive situations, preferred food and listening to music. Positive belief and worship are also factors that increase the ability to regulate individual emotions on internal factors.